2018
DOI: 10.1177/1066896918780343
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3 Ways of Dissecting the Pancreatoduodenectomy Specimen and Their Impact in the Lymph Node Count and the Lymph Node Metastatic Ratio

Abstract: The Adsay technique for LN retrieval was associated with a better LN count, more cases with LNM, and an LNR >0.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Diverse opinions exist whether perpendicular sectioning of uncinate/SMA and posterior surface/margin leads to inaccurate or an overestimation of total lymph node count. A recent comparison study of all 3 grossing protocols showed that the bivalve protocol yielded more lymph node count and lymph node metastasis than the other 2 grossing protocols, supporting that different grossing protocols can affect lymph node yield 45. However, both axial and bivalve protocols require perpendicular sectioning of uncinate/SMA and posterior surface/margins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse opinions exist whether perpendicular sectioning of uncinate/SMA and posterior surface/margin leads to inaccurate or an overestimation of total lymph node count. A recent comparison study of all 3 grossing protocols showed that the bivalve protocol yielded more lymph node count and lymph node metastasis than the other 2 grossing protocols, supporting that different grossing protocols can affect lymph node yield 45. However, both axial and bivalve protocols require perpendicular sectioning of uncinate/SMA and posterior surface/margins.…”
Section: Discussionmentioning
confidence: 99%
“…A recent comparison study of all 3 grossing protocols showed that the bivalve protocol yielded more lymph node count and lymph node metastasis than the other 2 grossing protocols, supporting that different grossing protocols can affect lymph node yield. 45 However, both axial and bivalve protocols require perpendicular sectioning of uncinate/SMA and posterior surface/margins. Therefore, this controversial result does not necessarily support one or the other grossing protocol.…”
Section: Interpretations Of Pt4 Categorymentioning
confidence: 99%
“…This method is beneficial, especially in evaluating intraductal lesions such as intraductal papillary mucinous neoplasms and ampullary tumors and does not require entire submission of the pancreas. In a recent comparative study, it was also found to be associated with a better lymph node yield and lymph node ratio [22]. However, R1 rate is reportedly lower in specimens grossed by the bivalving method, and inadequate sampling of the margins and free surfaces was thought to be the reason for the low R1 rate [15].…”
Section: Grossing Protocols and R0/r1 Statusmentioning
confidence: 99%